Safety and immunogenicity of an inactivated recombinant Newcastle disease virus vaccine expressing SARS-CoV-2 spike: Interim results of a randomised, placebo-controlled, phase 1 trial. (March 2022) - Pitisuttithum, Punnee; Luvira, Viravarn; Lawpoolsri, Saranath; Muangnoicharoen, Sant; Kamolratanakul, Supitcha; Sivakorn, Chaisith; Narakorn, Piengthong; Surichan, Somchaiya; Prangpratanporn, Sumalee; Puksuriwong, Suttida; Lamola, Steven; Mercer, Laina D.; et al.
Summary: Background: Production of affordable coronavirus disease 2019 (COVID-19) vaccines in low- and middle-income countries is needed. NDV-HXP-S is an inactivated egg-based recombinant Newcastle disease virus vaccine expressing the spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It's being developed by public sector manufacturers in Thailand, Vietnam, and Brazil; herein are initial results from Thailand. Methods: This phase 1 stage of a randomised, dose-escalation, observer-blind, placebo-controlled, phase 1/2 trial was conducted at the Vaccine Trial Centre, Mahidol University (Bangkok). Healthy males and non-pregnant females, aged 18–59 years and negative for SARS-CoV-2 antibodies, were eligible. Participants were randomised to receive one of six treatments by intramuscular injection twice, 28 days apart: 1 µg, 1 µg+CpG1018 (a toll-like receptor 9 agonist), 3 µg, 3 µg+CpG1018, 10 µg, or placebo. Participants and personnel assessing outcomes were masked to treatment. The primary outcomes were solicited and spontaneously reported adverse events (AEs) during 7 and 28 days after each vaccination, respectively. Secondary outcomes were immunogenicity measures (anti-S IgG and pseudotyped virus neutralisation). An interim analysis assessed safety at day 57 in treatment-exposed individuals and immunogenicity through day 43 per protocol. ClinicalTrials.gov (NCT04764422). Findings: Between March 20 and April 23, 2021, 377 individuals were screened and 210 were enroled (35 per group); all received dose one; five missed dose two. The most common solicited AEs among vaccinees, all predominantly mild, were injection site pain (<63%), fatigue (<35%), headache (<32%), and myalgia (<32%). The proportion reporting a vaccine-related AE ranged from 5·7% to 17·1% among vaccine groups and was 2·9% in controls; there was no vaccine-related serious adverse event. The 10 µg formulation's immunogenicity ranked best, followed by 3 µg+CpG1018, 3 µg, 1 µg+CpG1018, and 1 µg formulations. On day 43, the geometric mean concentrations of 50% neutralising antibody ranged from 122·23 international units per mL (IU/mL; 1 µg, 95% confidence interval (CI) 86·40–172·91) to 474·35 IU/mL (10 µg, 95% CI 320·90–701·19), with 93·9% to 100% of vaccine groups attaining a ≥ 4-fold increase over baseline. Interpretation: NDV-HXP-S had an acceptable safety profile and potent immunogenicity. The 3 µg and 3 µg+CpG1018 formulations advanced to phase 2. Funding: National Vaccine Institute (Thailand), National Research Council (Thailand), Bill & Melinda Gates Foundation, National Institutes of Health (USA).